2017
DOI: 10.1007/s10549-017-4566-0
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer-related paraneoplastic neurologic disease

Abstract: PND symptoms often presented prior to BC diagnosis, with the BC biologic subtype characteristics typical of the general BC population. BC diagnoses were often made at younger ages than that of the general BC population and with later-stage disease. Roughly 75% of patients benefited from immunotherapy. These data provide helpful information to providers treating this population of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…PNSs are generally associated with certain types of tumors, such as small cell lung cancer, thymoma, breast cancer, ovarian cancer, Hodgkin and non-Hodgkin lymphoma, testicular cancer, and neuroblastoma [7]. Breast cancer-related PNSs are very rare, in fact, Murphy et al reported that only 56 cases had occurred in their institution (Mayo Clinic, USA) in the past 20 years [8]. The average age of patients was 50 years and most patients had hormone receptor (HR) positive and Her2 negative, stage II disease [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PNSs are generally associated with certain types of tumors, such as small cell lung cancer, thymoma, breast cancer, ovarian cancer, Hodgkin and non-Hodgkin lymphoma, testicular cancer, and neuroblastoma [7]. Breast cancer-related PNSs are very rare, in fact, Murphy et al reported that only 56 cases had occurred in their institution (Mayo Clinic, USA) in the past 20 years [8]. The average age of patients was 50 years and most patients had hormone receptor (HR) positive and Her2 negative, stage II disease [8].…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer-related PNSs are very rare, in fact, Murphy et al reported that only 56 cases had occurred in their institution (Mayo Clinic, USA) in the past 20 years [8]. The average age of patients was 50 years and most patients had hormone receptor (HR) positive and Her2 negative, stage II disease [8]. PNSs include paraneoplastic cerebellar degeneration (PCD), opsoclonus myoclonus syndrome (OMS), stiff person syndrome, paraneoplastic neuropathy, and paraneoplastic encephalomyelitis.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells are transported to lymph nodes or lymphatic organs to present antigen to CD4 + T, CD8 + T and B cells after apoptosis. Immune response secondary to enlargement of lymph nodes and organs with increased B and T lymphocytes occurs [ [15] , [16] , [17] , [18] , [19] ]. However B and T lymphocyte responses do not always produce an anti-tumoral response and sometimes are thought to cause autoantigen formation and autoimmunity triggering and/or paraneoplastic syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…PND is a rare disease. From all cases of PND and breast cancer, 3.6% are related to PLE . From all cases with PLE, breast cancer is the second most common tumor, representing 4.5% to 8% of all cases .…”
Section: Discussionmentioning
confidence: 99%